Utility of Whole-Body CT Imaging in the Post Mortem Detection of Elder Abuse and Neglect in Maryland, 2007 - Daly, Barry ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. The general and original hypothesis to be explored in this study was that multi-slice computed tomography (CT) imaging of decedents in whom elder abuse was suspected or reported might enhance the work of the medical examiner by providing novel information not readily available at conventional autopsy and/or by ruling out the need for complete conventional autopsy in cases in which abuse findings were negative, thereby providing: time and cost efficiencies, additional evidentiary support in the form of state-of-the-art images, and, in some cases, compassionate support for families whose religions or cultures required more rapid and/or noninvasive techniques. No quantitative or qualitative data are available with this study. The data are comprised of the images taken from the autopsies of 57 decedents.